2020
DOI: 10.1093/jat/bkaa017
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phase I Metabolism of the Recently Emerged Synthetic MDMB-4en-PINACA and Its Detection in Human Urine Samples

Abstract: MDMB-4en-PINACA (methyl (S)-3,3-dimethyl-2-(1-(pent-4-en-1-yl)-1H-indazole-3-carboxamido)butanoate) is a recently emerged synthetic cannabinoid in Turkey. MDMB-4en-PINACA was detected in herbal material investigated by the Council of Forensic Medicine, Istanbul Narcotics Department in Turkey in April 2019. MDMB-4en-PINACA was added to the drug abuse list and quickly reported in biological samples after its first detection. In this study, the in vitro metabolism of MDMB-4en-PINACA was investigated by using a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Ester hydrolysis plus dehydrogenation metabolite (B20) was the second most abundant major metabolite in the HLM model, similar to the in-vivo findings where it is the second most prevalent metabolite detected in 18/20 urine samples (Table 2). Ester hydrolysis with dehydrogenation formed invivo in this study was also reported among other indazole carboxamide type SCBs with tert-leucine methyl ester moieties such as 5F-MDMB-PINACA [15] and MDMB-4en-PINACA [39,40]. This biotransformation was reported by both Krotulski et al [5].…”
Section: Discussionsupporting
confidence: 84%
“…Ester hydrolysis plus dehydrogenation metabolite (B20) was the second most abundant major metabolite in the HLM model, similar to the in-vivo findings where it is the second most prevalent metabolite detected in 18/20 urine samples (Table 2). Ester hydrolysis with dehydrogenation formed invivo in this study was also reported among other indazole carboxamide type SCBs with tert-leucine methyl ester moieties such as 5F-MDMB-PINACA [15] and MDMB-4en-PINACA [39,40]. This biotransformation was reported by both Krotulski et al [5].…”
Section: Discussionsupporting
confidence: 84%
“…Based on this finding, its metabolite, MDMB‐4en‐PINACA 3,3‐dimethylbutanoic acid (Figure 2), was prioritized for addition to the library database for identification in cases where urine samples were submitted. Metabolic profiles for methyl ester synthetic cannabinoids, including MDMB‐4en‐PINACA, have been well documented, and this species was reported as a primary metabolite and reasonably biomarker for monitoring use of MDMB‐4en‐PINACA 16,17 …”
Section: Resultsmentioning
confidence: 99%
“…Norman et al reported the detection of MDMB‐4en‐PINACA on drug‐infused papers from Scottish prisons in June 2019 15 . Ozturk et al reported the detection of MDMB‐4en‐PINACA in an herbal product from Turkey in April 2019 16 . In this study, toxicology testing of urine samples collected from suspected drug‐using individuals was monitored for the presence of MDMB‐4en‐PINACA metabolites; researchers identified 56 positive specimens (2.6% positivity).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…To date, MMB022 has been identified in seizures in Sweden (July 2018) and in Hungary (February 2019), as well as test purchases in Slovenia (July 2018) and in Germany (January 2019), but not yet reported in biological samples. In comparison, MDMB-4en-PINACA, a synthetic cannabinoid analog with an alkene, has been identified in authentic biological samples, 7,8 and has become increasingly prevalent in infused papers at Scottish prisons since June 2019. 9 Due to the structural similarity, MMB022 might become one of the next prevalent cannabinoids.…”
mentioning
confidence: 99%